An Innovative Multidisciplinary Strategy for Improving Students' Capacity for Computational Thinking: The Harezmi Education Model - Kert, Serhat Bahadir; Erkoc, Mehmet Fatih; Tonbuloglu, Betul (SPRINGER INT PUBL AG, 2026)
Since 2016, various districts in Turkey, especially schools in Istanbul, have implemented the Harezmi Education Model, an integrative approach. This approach encourages students to devise answers to real-world problems with the guidance of educators from diverse disciplines. This model's collaborative approach to problem-solving and project development has swiftly garnered notice, leading to its implementation in other schools. The core components of the methodology are computational thinking, algorithmic reasoning, Trcollaboration, and human-centered problem-solving processes. Plans are underway to implement the Harezmi Education Model statewide in 2024 as it continues to evolve. The model is achieving worldwide acclaim. This study sought to assess the impact of the Harezmi Education Model on the sub-dimensions of students' computational thinking self-efficacy perceptions. The Harezmi practices, held in Istanbul from October 2022 to May 2023, involved 868 pupils. The poll encompassed 1,573 children from 26 districts of Istanbul, including 705 students in the cohort. The results indicated that the Harezmi Education Model had a positive and statistically significant effect on the sub-dimensions of students' computational thinking self-efficacy perceptions, irrespective of gender.
Keywords: Harezmi Education Model; Computational thinking; Algorithmic thinking; Interdisciplinary education; K-12; Education & Educational Research